2017
DOI: 10.1103/physrevb.96.195424
|View full text |Cite
|
Sign up to set email alerts
|

Fast pulse sequences for dynamically corrected gates in singlet-triplet qubits

Abstract: We present a set of experimentally feasible pulse sequences that implement any single-qubit gate on a singlet-triplet spin qubit and demonstrate that these new sequences are up to three times faster than existing sequences in the literature. We show that these sequences can be extended to incorporate built-in dynamical error correction, yielding gates that are robust to both charge and magnetic field noise and up to twice as fast as previous dynamically corrected gate schemes. We present a thorough comparison … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…While this is often a good approximation 19 , the noise in actual experimental systems is known to follow a power-law spectrum 16,53 (1/f α ). We see, however, from the previous work 44,45 that, even in this scenario, similar approaches to that which we adopt here to combat the effects of noise still result in noticeable improvement in gate fidelities. We thus expect similar results for the capacitively-coupled qubits considered here.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…While this is often a good approximation 19 , the noise in actual experimental systems is known to follow a power-law spectrum 16,53 (1/f α ). We see, however, from the previous work 44,45 that, even in this scenario, similar approaches to that which we adopt here to combat the effects of noise still result in noticeable improvement in gate fidelities. We thus expect similar results for the capacitively-coupled qubits considered here.…”
Section: Discussionmentioning
confidence: 53%
“…Three papers have been written using the supcode technique, one for the case in which only (electrical) charge noise is present 43 and two others in which (magnetic) field noise is also included 44,45 . This method, which we will be employing a generalization of in this work, consists of inserting an uncorrected "identity" operation into the pulse sequence for a given gate that is arranged in such a way as to cancel the noise-induced error to leading order.…”
Section: % Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Several theoretical approaches have been proposed to mitigate the noise effects and improve the gate fidelities, including, for example, pulse engineering [ 18 ] and dynamically corrected gates. [ 19–23 ] Recently, it has been demonstrated that strongly microwave‐driven operations near the detuning sweet spots can effectively suppress the charge noises. [ 10,12,24–27 ] Despite these progresses, experimental gate fidelities are still below 90% [ 10 ] owing to the residual charge noise.…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] It is important to understand the underlying decoherence mechanisms to further extend the coherence time of a qubit for high‐fidelity quantum gates. [ 42–50 ] Other aspects that are as important as decoherence are to increase the single‐spin gate speed through electric dipole spin resonance (EDSR), [ 51–61 ] improve robustness against noise through quantum control sequences or qubit encoding, [ 62–83 ] and design qubits for better scalability. [ 34–38,84–89 ] There are also theoretical studies of the quantum error correction scheme to suppress errors of spin qubits.…”
Section: Introductionmentioning
confidence: 99%